A comparative study of robot‐assisted and open radical prostatectomy in 10 790 men treated by highly trained surgeons for both procedures. (12th April 2019) - Haese, Alexander; Knipper, Sophie; Isbarn, Hendrik; Heinzer, Hans; Tilki, Derya; Salomon, Georg; Michl, Uwe; Steuber, Thomas; Budäus, Lars; Maurer, Tobias; Tennstedt, Pierre; Huland, Hartwig; et al.
Abstract : Objective: To compare oncological, functional and surgical outcomes of open retropubic radical prostatectomy (ORP) vs robot‐assisted laparoscopic radical prostatectomy (RARP). Patients and methods: We identified 10 790 consecutive treated patients within our prospective database (2008–2016) who underwent either ORP (7007 patients) or RARP (3783). All procedures were performed by seven highly trained surgeons performing both surgical approaches regularly. Oncological (48‐month biochemical recurrence [BCR] rate), functional (urinary continence, erectile function), and surgical outcomes (rate of nerve‐sparing [NS] procedures, lymph node yield, surgical margin [SM] status, length of hospital stay [LOS], operation time, blood loss, transfusion rate, time to catheter removal) were assessed. Kaplan–Meier, multivariable Cox and logistic regression models were used to test for BCR and functional outcome differences. Results: No statistically significant difference regarding oncological outcome distinguished between ORP vs RARP. For functional outcomes, the 1‐week continence rates were higher in the ORP group (25.8% vs 21.8%, P  < 0.001). At 3 months, no statistically significant differences were observed. At 12 months, continence rates were modestly higher in the RARP group (90.3% vs 88.8%, P  = 0.01). This effect was no longer observed after stratification for age‐groups. The 12‐month potency rates were similar in ORP vs RARP (80.3% vs 83.6%, P  = 0.33). For surgical outcomes, there was no significant difference in the rates of NS procedures, lymph node yield, SM status, and LOS. Conversely, operation time was shorter in ORP, and blood loss, transfusion rates and time to catheter removal were significantly lower in RARP. Conclusions: Both surgical approaches, performed in a high‐volume centre by the same surgeons, achieve excellent, comparable oncological and functional outcomes. However, a modest advantage for RARP for surgical outcomes was observed, most likely attributable to its minimally invasive nature, and better teaching capabilities. Consequently, more than the surgical approach itself, the well‐trained surgeon remains the most important factor to achieve satisfactory outcomes.